lncRNA MIAT/HMGB1 Axis Is Involved in Cisplatin Resistance via Regulating IL6-Mediated Activation of the JAK2/STAT3 Pathway in Nasopharyngeal Carcinoma - Zhu, Xuewei; Liu, Li; Wang, Yang; Cong, Jianan; Lin, Zhang; Wang, Yongsen; Liu, Qi; Wang, Leiming; Yang, Ben; Li, Tao (Frontiers in Oncology, 2021)
Cisplatin-based chemotherapy and radiotherapy are the main first-line treatment strategies for nasopharyngeal carcinoma (NPC) patients. Unfortunately, resistance is a major obstacle in the clinical management of NPC patients. We prove that the expression level of high-mobility group box 1 (HMGB1) is dramatically increased in resistant NPC cells than that in sensitive cells. HMGB1 induces the expression and secretion of IL6, which leads to constitutive autocrine activation of the JAK2/STAT3 pathway and eventually contributes to chemoresistance in NPC cells. Long non-coding RNAs (lncRNAs) have been identified as key regulators involved in drug resistance. In this study, using GO analysis of the biological process and differential expression analysis, we find 12 significantly altered IncRNAs in NPC cell lines, which may be involved in regulating gene expression. Furthermore, we determine that elevated lncRNA MIAT level upregulates HMGB1 expression, contributing to cisplatin resistance in NPC cells. We find that the deficiency of the lncRNA MIAT/HMGB1 axis, inhibition of JAK2/STAT3, or neutralization of IL6 by antibodies significantly re-sensitizes resistant NPC cells to cisplatin in resistant NPC cells. Moreover, we provide the in vivo evidence that the deficiency of HMGB1 reduces cisplatin-resistant tumor growth. Most importantly, we provide clinical evidence showing that the expression level of the lncRNA MIAT/HMGB1/IL6 axis is elevated in resistant NPC tumors, which is highly correlated with poor clinical outcome. Our findings identify a novel chemoresistance mechanism regulated by the lncRNA MIAT/HMGB1/IL6 axis, which indicates the possibilities for lncRNA MIAT, HMGB1, and IL6 as biomarkers for chemoresistance and targets for developing novel strategies to overcome resistance in NPC patients.